Criminal law or penal law: which one is it? - Torralbo Muñoz, Bartolomé (Docencia y Derecho, 2023)
The teaching of Spanish Law in English responds to the dynamics of European integration and to the set of policies carried out in the European Higher Education Area. By offering training in English, universities can enhance the linguistic training of their graduates, improve their understanding of other legal systems, and attract international students. However, this objective is accompanied by several challenges. The first of these is the need for both teachers and students to be proficient in the language. The transition to an English language curriculum requires a high level of linguistic competence on the part of teachers along with continuous language improvement. Similarly, students must possess the language skills necessary to understand complex legal concepts and to participate effectively in debates. Teaching Spanish national law in English poses specific challenges, such as pedagogical adjustments, creating legal materials in English and achieving linguistic clarity while maintaining legal precision. Specific problems arise in the context of criminal law, such as navigating nuanced legal terminology, understanding different legal systems, or explaining legal categories that do not exist in other jurisdictions.